Implications on Professional Practice and Provider Support: A Commentary on the Manuscript "The Impact of Patient Suicidal Behavior on the Personal and Professional Well-Being of Mental Health Providers: A Systematic Review" - Neal-Walden, Tracy A.; Linkh, David J. (Clinical psychology (New York, N.Y.), 2023)
MacGarry et al. (2022) have provided an informative systematic review of the impact of patient suicidal behavior on the personal and professional well-being of mental health teams. Their review synthesized quantitative and qualitative studies on this subject and included mixed methods studies as well. This study provides robust evidence of the considerable impact of suicide on mental health professionals. The authors concluded similarly to previous reviews (Sandford et al., 2021; Séguin et al., 2014) that the experience of losing a patient through suicide may have both a significant professional and personal impact on mental health professionals but extended the findings by highlighting multiple vulnerability factors which may moderate the level of impact on the mental health professional. Thus, the organizational response should be adapted to be more person-centered vs risk management focused. Our commentary will focus on the overarching themes identified in the review that we believe warrant further attention to include the impact of suicide and suicide behavior and implications related to professional practice, provider support, mental health policy, and research. (PsycInfo Database Record (c) 2025 APA, all rights reserved) (Source: journal abstract)